Pengaruh Persiapan Pranikah terhadap Kejadian Stunting (Studi Kasus di Wilayah Kerja Puskesmas Muara Dua Lhokseumawe) - Nizan Mauyah; Subki Subki; Nora Usrina (Universitas Malahayati Lampung, 2024)
ABSTRACT Stunting is a growth problem in early childhood that requires special attention. Growth and development disorders are reflected in the average height of children of their age. Children who suffer from stunting are at risk of experiencing delayed brain development which affects intelligence. If intervention is not provided as early as possible, they face learning difficulties at school, and face barriers to participating in the community. To determine the effect of premarital preparation on the incidence of stunting. This research is an observational study with a cross-sectional approach. The population in this study were mothers who had toddlers and before becoming pregnant, they prepared for their pregnancy starting from catin who came to the Muara Health Center. The sample size for accidental sampling was all mothers with toddlers who came to the Muara Dua Health Center in the Lhokseumawe City Working Area. Data collection was carried out by distributing questionnaires. Data were analyzed using Univariate and Bivariate statistics using the chi-square test with the help of SPSS computerization, at a confidence level of 95% (α=0.05). This research was conducted in the Muara Dua Lhokseumawe health center working area from May to August 2024 using a questionnaire. Based on statistical tests in bivariate analysis with the chi square test at a confidence level of 95%, the value obtained was p=0.003 (p0.05). This means that there is a significant relationship between premarital preparation and the incidence of stunting in children. There is a relationship between pre-wedding preparation and the incidence of stunting in children in the Muara Dua Community Health Center working area, Lhokseumawe City. Keywords: Stunting, Toddlers, Pre-Wedding Preparations ABSTRAK Stunting merupakan masalah pertumbuhan pada anak usia dini yang memerlukan perhatian khusus. Gangguan pertumbuhan dan perkembanganya tercermin dari rata-rata tinggi badan anak seusianya. Anak-anak yang menderita stunting beresiko mengalami keterlambatan perkembangan otak yang berpengaruh kepada kecerdasan. Jika tidak diberikan intervensi sedini mungkin, mereka menghadapi kesulitan belajar di sekolah, dan menghadapi hambatan untuk berpartisipasi dalam komunitas. Mengetahui pengaruh persiapan pranikah terhadap kejadian stunting. Penelitian ini merupakan penelitian observasional dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah ibu-ibu yang mempunyai balita dan sebelum hamil mempersiapkan kehamilannya dimulai dari catin yang datang ke Puskesmas Muara. Besar sampel accidental sampling yaitu seluruh ibu-ibu yang mempunyai balita yang datang ke Puskesmas Muara Dua di Wilayah Kerja Kota Lhokseumawe. Pengumpulan data dilakukan dengan penyebaran kuesioner. Data dianalisis menggunakan statistik Univariat, Bivariat menggunakan uji chi–squre test dengan bantuan komputerisasi SPSS, pada tingkat kepercayaan 95% (α=0,05). Penelitian ini dilakukan di wilayah kerja puskesmas Muara Dua Lhokseumawe dari bulan Mei sampai dengan Agustus 2024 dengan menggunakan kuesioner. Berdasarkan uji statistik pada analisis bivariat dengan uji chi-square pada tingkat kepercayaan 95%, diperoleh nilai p=0,003 (p0,05). Artinya ada hubungan yang bermakna antara persiapan pranikah dengan kejadian stunting pada anak. Ada hubungan antara persiapan pranikah dengan kejadian stunting pada anak di wilayah kerja Puskesmas Muara Dua Kota Lhokseumawe Kata Kunci: Stunting, Balita, Persiapan Pranikah